KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE (TTW) - Sisca Bunga Dwi Ariani Astuti; Nila Kesumawati; Ety Septiati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The ability of mathematical communication is a capability that must be possessed by students in learning mathematics. Mathematical communication is the ability to convey mathematical ideas, both oral and written and the ability to understand and accept other people's mathematical ideas carefully, analytically, critically, and evaluatively to sharpen understanding. Cooperative Learning is one of the appropriate learning strategies to engage students in actively communicating between teachers and students as well as students and students in small groups of 4-5 people with heterogeneous group structures. Think-Talk-Write type cooperative learning begins with how students think about completing a task or problem, followed by communicating their thoughts through discussion forums, and finally through the discussion forum students can rewrite their thoughts. Keywords— Mathematical Communication, Cooperative Learning, Think-Talk-Write (TTW) Abstrak— Kemampuan komunikasi matematis merupakan kemampuan yang harus dimiliki oleh siswa dalam pembelajaran matematika. Komunikasi matematis adalah kemampuan menyampaikan gagasan/ide matematis, baik secara lisan maupun tulisan serta kemampuan memahami dan menerima gagasan/ide matematis orang lain secara cermat, analitis, kritis, dan evaluative untuk mempertajam pemahaman. Pembelajaran Kooperatif adalah salah satu strategi pembelajaran yang tepat untuk melibatkan siswa dalam berkomunikasi secara aktif baik antara guru dan siswa maupun siswa dan siswa dalam kelompok kecil 4-5 orang dengan struktur kelompok yang bersifat heterogen. Pembelajaran kooperatif tipe Think-Talk-Write dimulai dengan bagaimana siswa memikirkan penyelesaian suatu tugas atau masalah, kemudian diikuti dengan mengkomunikasikan hasil pemikirannya melalui forum diskusi, dan akhirnya melalui forum diskusi tersebut siswa dapat menuliskan kembali hasil pemikirannya. Kata Kunci— Komunikasi matematis, Pembelajaran Kooperatif, Think-Talk-Write (TTW)